A decade of developing applications exploiting the properties of polyelectrolyte multilayer capsules. Issue 7 (6th December 2022) - Li, Jie; Parakhonskiy, Bogdan V.; Skirtach, Andre G.
Abstract : Various methods of encapsulation into and release from polyelectrolyte multilayer capsules are used to develop diverse applications. Abstract : Transferring the layer-by-layer (LbL) coating approach from planar surfaces to spherical templates and subsequently dissolving these templates leads to the fabrication of polyelectrolyte multilayer capsules. The versatility of the coatings of capsules and their flexibility upon bringing in virtually any material into the coatings has quickly drawn substantial attention. Here, we provide an overview of the main developments in this field, highlighting the trends in the last decade. In the beginning, various methods of encapsulation and release are discussed followed by a broad range of applications, which were developed and explored. We also outline the current trends, where the range of applications is continuing to grow, including addition of whole new and different application areas.